Taxonomic papers on Collembola in Zootaxa, 2001 to 2020 - Greenslade, Penelope; Weiner, Wanda Maria (Zootaxa, 2021)
We summarise here publications on Collembola in the journal Zootaxa over the years 2001 to 2020 and include numbers and nationalities of authors and referees. We also list numbers of new species and genera described. For a relatively small pool of taxonomists, we conclude their output has been considerable and Zootaxa has provided a useful vehicle in which to publish their research findings. Of interest, is the shift away from a Eurocentric origin of authors to a Chinese and Brazilian one. Reasons for this change are suggested.